Asymmetric bone adaptations to soleus mechanical loading after spinal cord injury - Dudley-Javoroski, S. (2008)
The purpose of this report is to examine longitudinal bone mineral density (BMD) changes in individuals with spinal cord injury (SCI) who began unilateral soleus electrical stimulation early after injury. Twelve men with SCI and seven without SCI underwent peripheral quantitative computed tomography assessment of distal tibia BMD. After 4.5 to 6 years of training, average trained limb BMD was 27.5% higher than untrained limb BMD. The training effect was more pronounced in the central core of the tibia cross-section (40.5% between-limb difference). No between-limb difference emerged in the anterior half of the tibia (19.2 mg/cm(3) difference, p>0.05). A robust between-limb difference emerged in the posterior half of the tibia (76.1 mg/cm(3) difference, p=0.0439). The posterior tibia BMD of one subject remained within the range of non-SCI values for 3.8 years post-SCI. The results support that the constrained orientation of soleus mechanical loads, administered over several years, elicited bone-sparing effects in the posterior tibia. This study provides a demonstration of the bone-protective potential of a carefully controlled dose of mechanical load. The specific orientation of applied mechanical loads may strongly influence the manifestation of BMD adaptations in humans with SCI.